Extraction of spin observables in baryon-baryon scattering, sensitive to gluon- and quark-exchange effects - Bondarenco, M.V. (Вопросы атомной науки и техники, 2007)
Spin-dependent characteristics of baryon-baryon scattering are discussed, in which QCD dynamics is expected to display itself in most simply treatable regimes: 1). being dominated by semi-classical gluonic field without dynamical quarks; 2). as perturbative scattering. It is argued that peripheral semi-classical gluon exchange can make a major contribution to the pseudovector scattering amplitude, whereas one of the tensor amplitude components must be seeded by quark exchange, thus containing a hard scale and allowing for perturbative treatment. Expressions for absolute values of the promising amplitudes are derived in terms of double spin asymmetries in NN-scattering. Options for realization of corresponding polarization measurements in strange hyperon collisions with nucleons are analysed, along with consistency tests supplied by additional spin amplitudes emerging in non-identical. Обговорюються спінові характеристики баріон-баріонного розсіяння, в яких очікуються найменш замасковані прояви КХД ступенів свободи: 1) у квазикласичному глюонному режимі без динамічних кварків; 2) в пертурбативному режимі. Показано, що квазикласичний глюонний обмін найбільш виразно проявляється у псевдовекторній амплітуді розсіяння, тоді як тензорні спінові амплітуди дозволяють виділити процеси обміну кварками, що привносять відносно жорсткий імпульсний масштаб. Запропоновано вирази для абсолютних величин амплітуд, що обговорюються, через двоспінові асиметрії в пружному NN-розсіянні. Обговорюються можливості проведення відповідних поляризаційних вимірів у зіткненнях дивних гіперонів з нуклонами, а також інформація, що надається додатковими амплітудами у цих процесах. Обсуждаются спиновые характеристики барион-барионного рассеяния, в которых ожидается наименее замаскированное проявление КХД степеней свободы: 1) в квазиклассическом глюонном режиме без динамических кварков; 2) в пертурбативном режиме. Показано, что квазиклассический глюонный обмен наиболее отчетливо проявляется в псевдовекторной амплитуде рассеяния, тогда как тензорные спиновые амплитуды позволяют выделить процессы обмена кварками, содержащие относительно жесткий импульсный масштаб. Предложены выражения для абсолютных величин обсуждаемых амплитуд через двуспиновые асимметрии в упругом NN-рассеянии. Обсуждаются варианты проведения соответствующих поляризационных измерений в столкновениях странных гиперонов с нуклонами, и информация, предоставляемая появляющимися в этих процессах дополнительными амплитудами.